If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24xy + -20by + 18x + -15b = 0 Reorder the terms: -15b + -20by + 18x + 24xy = 0 Solving -15b + -20by + 18x + 24xy = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-18x' to each side of the equation. -15b + -20by + 18x + -18x + 24xy = 0 + -18x Combine like terms: 18x + -18x = 0 -15b + -20by + 0 + 24xy = 0 + -18x -15b + -20by + 24xy = 0 + -18x Remove the zero: -15b + -20by + 24xy = -18x Add '-24xy' to each side of the equation. -15b + -20by + 24xy + -24xy = -18x + -24xy Combine like terms: 24xy + -24xy = 0 -15b + -20by + 0 = -18x + -24xy -15b + -20by = -18x + -24xy Reorder the terms: -15b + -20by + 18x + 24xy = -18x + 18x + -24xy + 24xy Combine like terms: -18x + 18x = 0 -15b + -20by + 18x + 24xy = 0 + -24xy + 24xy -15b + -20by + 18x + 24xy = -24xy + 24xy Combine like terms: -24xy + 24xy = 0 -15b + -20by + 18x + 24xy = 0 The solution to this equation could not be determined.
| 3x^2+9x-2x-6= | | a+7b+a+3c= | | (4x+1)(4x+1)=(3x-1)(3x-1) | | 36x+12x^2-12xy= | | 4x-5y+9+2x-y-14= | | 2x(x^4+6x^3+8x^2-6x-9)=0 | | 10(s-4)=-119 | | 15x^2+26x+8= | | 8+k=3 | | 3(2)(2)+2= | | C/20-42=59 | | x+x(x+1)+(x+2)=24 | | 8x+8y=-16 | | 12.9+-2.2= | | 6x-6=4x+34 | | 12ax-y+2ay-6x= | | -8(2a+5)-4= | | 13.7+-0.1+-2.4= | | -3(-5p+8)-p= | | 2+7y=11-y-y | | 5x(5x+2)-(5x+2)= | | 6x-1=3x-43 | | 2(1-2y)+5y=3 | | 9y-2y+8=4y+38 | | 200-7x=95 | | 3025=x^2+.5625x^2 | | 5k-8=13-2k | | 2?5=-z?45 | | 10w-4w-w+2+w+9= | | 9x-(7x+6)=6 | | 2(3x-4)-10=5(x+4) | | (17x)^(1/2) |